The dynamic universe: realizing the potential of classical time domain and multimessenger astrophysics - Howell, Steve B.; Howell, D. Andrew; Street, R. A.; Soares-Furtado, Melinda; Jackson, Brian; Greene, Thomas P. (Frontiers in Astronomy and Space Sciences, 2024)
In parallel with the multi-messenger revolution, major advances in time-domain astronomy across multiple science disciplines relevant to astrophysics are becoming more urgent to address.Aside from electromagnetic observations of gravitational wave events and explosive counterparts, there are a number of "classical" astrophysical areas that require new thinking for proper exploration in the time domain. How NASA, NSF, ESA, and ESO consider the 2020 USA Decadal Survey within the astronomy community, as well as the worldwide call to support and expand time domain and multi-messenger astrophysics, it is crucial that all areas of astrophysics, including stellar, galactic, solar system, and exoplanetary science participate in the discussion, and that it not be made into an exclusive preserve of cosmological, high-energy, explosive and transient science. Time domain astronomy is used to explore many aspects of astrophysics -particularly concerning ground-and space-based mission science goals of exploring how the universe works, understanding how did we get here, and are we alone. Time domain studies are already built into the core operations of many currently operating and future space telescopes (e.g., Roman, PLATO) as well as current and planned large areal ground-based surveys (e.g., Rubin). Time-domain observations designed for one scientific purpose, also lead to great discoveries in many other science areas. The recent advent of user-friendly hardware, software, observational approaches, and online data infrastructure has also helped make time domain observations especially suitable and appealing for citizen science projects. We provide a review of the current state of TDAMM alerts and observational protocols, revealing a wide array of software and applications, much of which is incompatible. Any conversation regarding TDAMM astrophysics should include all aspects of the field, including those aspects seen as classical applications.1 Howell et al.